Age-dependent nasal immune responses in non-hospitalized bronchiolitis children - Cortegano, Isabel; Rodríguez, Mercedes; Hernángómez, Susana; Arrabal, Alejandro; Garcia-Vao, Carlos; Rodríguez, Javier; Fernández, Sandra; Díaz, Juncal; de la Rosa, Belén; Solís, Beatriz; Arribas, Cristina; Garrido, Felipe; et al. (Frontiers in Immunology, 2022)
Bronchiolitis in children is associated with significant rates of morbidity and mortality. Many studies have been performed using samples from hospitalized bronchiolitis patients, but little is known about the immunological responses from infants suffering from mild/moderate bronchiolitis that do not require hospitalization. We have studied a collection of nasal lavage fluid (NLF) samples from outpatient bronchiolitis children as a novel strategy to unravel local humoral and cellular responses, which are not fully characterized. The children were age-stratified in three groups, two of them (GI under 2-months, GII between 2-4 months) presenting a first episode of bronchiolitis, and GIII (between 4 months and 2 years) with recurrent respiratory infections. Here we show that elevated levels of pro-inflammatory cytokines (IL1β, IL6, TNFα, IL18, IL23), regulatory cytokines (IL10, IL17A) and IFNγ were found in the three bronchiolitis cohorts. However, little or no change was observed for IL33 and MCP1, at difference to previous results from bronchiolitis hospitalized patients. Furthermore, our results show a tendency to IL1β, IL6, IL18 and TNFα increased levels in children with mild pattern of symptom severity and in those in which non RSV respiratory virus were detected compared to RSV+ samples. By contrast, no such differences were found based on gender distribution. Bronchiolitis NLFs contained more IgM, IgG1, IgG3 IgG4 and IgA than NLF from their age-matched healthy controls. NLF from bronchiolitis children predominantly contained neutrophils, and also low frequency of monocytes and few CD4+ and CD8+ T cells. NLF from infants older than 4-months contained more intermediate monocytes and B cell subsets, including naïve and memory cells. BCR repertoire analysis of NLF samples showed a biased VH1 usage in IgM repertoires, with low levels of somatic hypermutation. Strikingly, algorithmic studies of the mutation profiles, denoted antigenic selection on IgA-NLF repertoires. Our results support the use of NLF samples to analyze immune responses and may have therapeutic implications.